Meta-analysis unravels common responses of seed oil fatty acids to temperature for a wide set of genotypes of different plant species - Alberio, Constanza; Aguirrezábal, Luis A. N. (Frontiers in Plant Science, 2024)
Temperature is the main environmental determinant of seed oil fatty acid composition. There are no models describing common responses of main seed oil fatty acids to temperature in plants. Metaphenomics tools were applied to a database consisted of 164 genotypes of 9 species, sunflower, rapeseed, soybean, maize, flax, chia, safflower, olive and camelia, grown under a wide range of environmental conditions. A General Model was established with data from four widely sown species. The minimum temperature during grain filling responses of fatty acids in the General Model were close to responses found in genotypes of five independent species used to validate the model. Dissections of the general model by selecting the appropriate data allowed unraveling previously unknown features of the response of fatty acid to the minimum temperature during grain filling. The response of fatty acids to temperature for any species was unaffected by experimental conditions (field or controlled conditions) during the oil synthesis stage. The oleic acid trait did not affect the response to temperature of fatty acids synthesized downstream and upstream of it. Traits such as high stearic or high linoleic did not affect the response of fatty acids synthesized upstream or downstream of the trait. The established models and new knowledge could be applied to design cost-effective and timely experiments to assess the potential responses of seed oil fatty acids to temperature of previously untested genotypes.